INVESTIGATION OF THE PHOTOMETRIC SYSTEM OF THE METEOR TV CCD CAMERAS - Kulichenko, M. O.; Maigurova, N. V.; Shulga, O. V. (Одеські астрономічні публікації, 2020)
The study of meteoroids and the phenomena arising from their entry into the Earth’s atmosphere is of considerable scientific and practical interest to obtain data on the origin and evolution of the solar system, to study the physics of planetary atmospheres, and to solve the problem of problem of asteroid-cometary-meteoroid hazard. Today the most effective and informative are photometric and spectral studies of meteor phenomena, which provide information on the chemical composition and physical properties (density, combustion temperature, etc.) of meteoroids that allow us to classify these bodies by parental origin and mineralogical structure. This paper presents the results of a study of the photometric system of eight meteor telescopes of the same type with a lens having a wide field of view (f = 50 mm, f / 1.2) and WAT-902H2 cameras. Telescopes equipped with broadband Cokin filters P050 (cyan) and P003 in the blue and red bands are installed in Mykolaiv and Odesa. An original method is used to observe meteors - the method of accumulation of shifted frames for TV cameras, which provide an accumulated image of reference stars in the form of points on a motionless telescope. In this work, simultaneous observations of reference stars in two filters obtained on 2 different observation nights were used. Cross-identification of the observational data with the Gaia DR2 catalog showed that the standard error of the residual coordinate differences (Obs – Gaia DR2) is about 7 "for both coordinates in both filters. The bandwidths of our filters are closest to the photometric system Gaia BP / RP, which was selected as a standard system to which the obtained instrumental stellar magnitudes were transformed. Transformation coefficients for converting instrumental stellar magnitudes into Gaia BP/RP photometric system were obtained by linear regression. Average standard photometric solution errors were 0.2 mag and 0.3 mag for red i and blue band, respectively. The possibility of determining the color index based on the array of common stars from observations in two bands is shown